Contextual-Based Extracurricular Management in Elementary School: A Good Practice from Taruna Papua Elementary School Timika (SATP) - Walewangko, Stief Aristo; Rawis, Joulanda Altje Meiske; Tambingon, Henny Nikolin; Wullur, Mozes Markus; Lomban, Edino Ayub; Tamboto, Fabyana Imelda; Mandolang, Eunike; Mangundap, Jelvi Monica (Yayasan Abdurrauf Cendekia Nusantara, 2025)
The objective of this research is to analyze the contextual-based extracurricular management implemented at Taruna Papua Timika Elementary School (SATP). The present research employs a qualitative methodology, specifically a case study approach, and utilizes six key informants who have implemented the program. A comprehensive investigation encompassing interviews, observations, documentation, and archival records was conducted to ascertain the management of contextual-based extracurricular programs. The findings of this investigation are: (1) The planning process is comprised of the following elements: directing the grand design of extracurricular programs; identifying the needs, potential, and interests of students (psychological examination); preparing extracurricular guidelines; arranging extracurricular financing; and, providing extracurricular facilities and infrastructure. (2) The organizing process consists of the following elements: registration and determination of extracurricular types and participants; recruitment and determination of extracurricular instructors; creation of extracurricular activity schedules; technical guidance and creation of extracurricular program targets and achievements; and formation of program supervisor teams. (3) The implementation process consists of the following elements: preparation of instructors; implementation of extracurricular sports, arts, and general knowledge; technical management of the program by instructors; and reporting in the form of daily journals. (4) Monitoring and evaluation consists of the following elements: program supervision; utilization of WhatsApp facilities; reporting of activity documentation; accountability for extracurricular equipment; monthly evaluations; end-of-semester evaluations, and the act of documenting the advancement of students in their academic pursuits. It is recommended that education stakeholders implement the aforementioned management process.